Korelasi Kualitas Tidur Pekerja Pabrik Dengan Kejadian Vertigo - Setyawan, Yuswanto (Jurnal Ilmiah Kesehatan, 2025)
Vertigo is a strange condition that is often not realized and/or undiagnosed in the workplace, characterized by dizziness, blurred vision, loss of balance, nausea and vomiting. The aim of this research is to determine the impact of sleep quality on the incidence of vertigo. This research is a quantitative cross sectional and was tested using the chi square test and Spearman correlation. This study used a population of all factory workers in the city of Sidoarjo. The sample used was 100 factory workers who experienced dizziness at least once a month. The questionnaire used is the Vertigo symptom scale. The results show that there is a relationship between the Sleep Quality variable and Vertigo with a strong relationship strength category with a correlation value of -0.572, meaning that 57% of sleep quality influences the incidence of vertigo in factory workers. Suggestions for future researchers can use qualitative methods with interviews to get more detailed results for each respondent. Suggestions for future researchers can use methods in the form of interviews.